2020
DOI: 10.1590/1678-5150-pvb-6165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the euthanasia of seropositive dogs for canine visceral leishmaniasis as the only method of controling the disease in the enzootic area in the Midwestern Minas Gerais

Abstract: Human Visceral Leishmaniasis (VL) is expanding, and it is distributed in the five geographic regions of Brazil, with the Northeast being the region that presents the most significant number of registered cases. The main urban reservoir of the etiological agent of VL is the domestic dog, and it is known that canine cases precede human cases. One of the control actions of VL, recommended by the Ministry of Health, is performing the euthanasia of seropositive dogs. In 2013, in the municipality of Iguatama/MG, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…These levels of infection are higher than those found in our study. Considering our results, we reiterate what has been discussed about the sensitivity of the different diagnostic methods for the diagnosis of canine VL (Lopes et al, 2017;Vaz et al, 2020). No test currently available has 100% specificity and sensitivity.…”
Section: Zanette Et Al (supporting
confidence: 71%
“…These levels of infection are higher than those found in our study. Considering our results, we reiterate what has been discussed about the sensitivity of the different diagnostic methods for the diagnosis of canine VL (Lopes et al, 2017;Vaz et al, 2020). No test currently available has 100% specificity and sensitivity.…”
Section: Zanette Et Al (supporting
confidence: 71%
“…Nesse estudo, 49,30% (71/144; p<0.0001) dos cães atendidos foram reagentes para anticorpos anti-L. infantum no TR DPP ® em amostras sanguíneas do Agreste e Sertão de Sergipe, sendo superior aos valores observados no Ceará (1,3%) (Batista et al, 2021), Minas Gerais (7,8%) (Vaz et al, 2020), São Paulo (8,70%) (D' Andréa et al, 2015), Paraíba (15,02%) (silva et al, 2021), Rio de Janeiro (26,3%) (Abrantes et al, 2018) e no Rio Grande do Sul (24,4%) (Mariga et al, 2021).…”
Section: Resultsunclassified
“…Nevertheless, studies such as those by Ashford et al [251], Costa et al [252], Nunes et al [253], Costa et al [254], and Bermudi et al [255] have shown that the elimination of infected dogs reduces the incidence of VL in humans and dogs. Conversely, some researchers have shown the opposite, such as Dantas-Torres et al [242], Dietze et al [256], Paranhos-Silva et al [257], and Vaz et al [258].…”
Section: The Challenges Of Controlling the Spread Of Canine Visceral ...mentioning
confidence: 98%